(3eHGOF GdEOGQI (B/s - (3ZGRj, cQje efUhQs ((3GdEScfOQjI(B: s (3ecJHI GdhaGA GdbGfhfjI(B, s, 2015)
(3jVe ebOeI aj GdEOGQI, GdHjFI,KbGaI GdefXeI hGdJfhY, GdEWGQ GdacQj ddEOGQI, GdJNWjW, GdJfXje GdEOGQj, GdJhLjg, GdQbGHI GdEOGQjI GdbjGOI GdEOGQjI , GdEJUGdGJ GdEOGQjI ,EJNGO GdbQGQGJ GdEOGQjI, EOGQI GdehGQO GdHTQjI , CNdGbjGJ GdEOGQI h GdeSDhdjI GdELJeGYjI ddefXeGJ , GdaQb Hjf GdEOGQI GdYGeI h EOGQI GdCYeGd, eONd GdEOGQI HGdCgOGa , GdEJLGgGJ GdeYGUQI aj GdEOGQIs
Keywords: (3EOGQI GdCYeGds; (3GdEOGQIs; (3GdEOGQI GdYGeIs; (3GdacQ GdEOGQjs